Imposições negociadas: poder, saber e inculcação de valores do livro didático de história : uma análise dos livros adotados pelo PNLD para o Ensino Médio no biênio 2010/2012 - Tourinho Júnior, Washington [UNESP] (2015)
This work analizes the role of the didatic book of History in the process of socialization of the egressed students of the school system, to do so, the books adopted by the public education system schools were chosen as the object of analysis, speceifically the books directed for high school students, in their single volume version, being understood that these books consist, in reality, of a strategic space of power distribution, seizure of knowledge and the conduction of an intense and gradual process of inculcation of values were structured the interpretative axes that make up the thesis; As a starting point the didatic book is analyzed in its multiple dimensions, observing, thereunto, the composing elements of the didatic book, such as: The protocol rules that give dimension to its production, its textual discourse as well as the formative element of this discourse and, at last, the role carried by the editing industry in the production of the existing didatic books of History; the following approach will be the analysis of the space of power distribution and appropriation of knowledge in which is positioned the didatic book of History. To do this, we'll analyze the relation between the school environment and the academic environment, as constituents of the educational process, as well as the role carried by the History subject, for its curriculum and the teachers' manuals in the definition of the objectives that should be fulfilled by the didatic books of History; In the third point we'll analyze the ways of production and authorization of the didatic text, centering our analyzes in two important conditioners: the State, through its programs, parameters and norms for the elaboration of didatic books, and the editing industry, as a fundamental element in the operacionalization of the productive process of these books; lastly, an individual analysis of the didatic books of the chosen...